2010
DOI: 10.1021/ja1024639
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Identification of Intermediates of Benzyl Chloride Reduction at a Silver Electrode by SERS Coupled with DFT Calculations

Abstract: Aiming to deeply understand the electrocatalytic mechanism of silver on reduction of benzyl chloride, we carried out an in situ electrochemical surface-enhanced Raman spectroscopic study to characterize various surface species in different electrode potential regions. A further analysis with DFT calculation reveals that the benzyl radical and its anionic derivate bonded on a silver electrode are the key intermediates, implying that the pathway could drastically differ from the outer sphere concerted electron r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
131
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 28 publications
9
131
0
4
Order By: Relevance
“…Detailed mechanistic analyses of the electrocatalytic process have been so far achieved for the reduction of aryl [3] and benzyl halides [16,17], in the latter case also with the support of a combined computational and SERS investigation [26,27], even if the computation-based mechanism published in reference [27] has recently been disproved by the same authors [28], agreeing with a previously published mechanism [16]. In the same context, detailed studies have been carried out on the role of single factors modulating the process, such as the reactant molecular structure (organic moiety and halide leaving group), the nature, morphology and state of the electrode surface [29], the adsorption of the reagents and products [30,31], and the role of the supporting electrolyte [32], while few preliminary studies have been reported concerning the role of the solvent [33][34][35], and a more systematic investigation is still overdue.…”
Section: Introductionmentioning
confidence: 97%
“…Detailed mechanistic analyses of the electrocatalytic process have been so far achieved for the reduction of aryl [3] and benzyl halides [16,17], in the latter case also with the support of a combined computational and SERS investigation [26,27], even if the computation-based mechanism published in reference [27] has recently been disproved by the same authors [28], agreeing with a previously published mechanism [16]. In the same context, detailed studies have been carried out on the role of single factors modulating the process, such as the reactant molecular structure (organic moiety and halide leaving group), the nature, morphology and state of the electrode surface [29], the adsorption of the reagents and products [30,31], and the role of the supporting electrolyte [32], while few preliminary studies have been reported concerning the role of the solvent [33][34][35], and a more systematic investigation is still overdue.…”
Section: Introductionmentioning
confidence: 97%
“…By using this peculiar metal, dehalogenation of the polyhalogenated organic compounds proceeded with very high efficiency. Such extraordinary electrocatalytic activities of Ag towards the reductive dehalogenation reaction of organic halides [23][24][25][26][27][28][29][30] and its exact mechanistic origin [31][32][33][34][35] have also well reported by a series of papers. In this paper, we have mainly investigated the role of pH on the dechlorination efficiency and electrochemical reduction behavior of chloroacetic acids on activated Ag electrodes in aqueous medium.…”
Section: Introductionmentioning
confidence: 82%
“…이러한 계면 에서 일어나는 반응을 관찰하기 위해 surface-enhanced infrared absorption spectroscopy(SEIRAS) 5) , attenuated total reflection-infrared(ATR-IR) spectroscopy 6) , 그리고 surface-enhanced Raman scattering(SERS) spectroscopy 7,8) 등이 이용되고 있는데, 특히 SERS는 매우 높은 민감도를 가지기 때문에 단일 분자 수준의 정보 …”
Section: )unclassified